Information Technology, Manpower Development and Organizational Performance - Baum, Bernard H.; Burack, Elmer H. (Academy of Management Journal, 1969)
This study of some 70 large business firms suggests that many companies, some of considerable size, continue to reflect a lack of appreciation for uses of information technology in managerial decision systems and the implications of this innovation for managerial education and training. This research additionally confirms the necessary organizational rearrangements and attendant programs at all organization levels which accompany the successful extension of computer based systems.